The eEF1A Proteins: At the Crossroads of Oncogenesis, Apoptosis, and Viral Infections - Abbas, Wasim; Kumar, Amit; Herbein, Georges (Frontiers in Oncology, 2015)
Eukaryotic translation elongation factors 1 alpha, eEF1A1 and eEF1A2, are not only translation factors, but also pleiotropic proteins that are highly expressed in human tumors, including breast cancer, ovarian cancer and lung cancer. eEF1A1 modulates cytoskeleton, exhibits chaperone-like activity and also controls cell proliferation and cell death. By contrast eEF1A2 protein favors oncogenesis as shown by the fact that overexpression of eEF1A2 leads to cellular transformation and gives rise to tumors in nude mice. The eEF1A2 protein stimulates the phospholipid signaling and activates the Akt-dependent cell migration and actin remodeling that ultimately favors tumorigenesis. By contrast, inactivation of eEF1A proteins leads to immunodeficiency, neural and muscular defects, and favors apoptosis. Finally, eEF1A proteins interact with several viral proteins resulting in enhanced viral replication, decreased apoptosis and increased cellular transformation. This review summarizes the recent findings on eEF1A proteins indicating that eEF1A proteins play a critical role in numerous human diseases through enhancement of oncogenesis, blockade of apoptosis and increased viral pathogenesis.